Retinal blood vessel diameters in children and adults exposed to a simulated altitude of 3,000 m - Mlinar, Tinkara; Debevec, Tadej; Kapus, Jernej; Najdenov, Peter; McDonnell, Adam C.; Ušaj, Anton; Mekjavic, Igor B.; Jaki Mekjavic, Polona (Frontiers in Physiology, 2023)
Introduction: Technological advances have made high-altitude ski slopes easily accessible to skiers of all ages. However, research on the effects of hypoxia experienced during excursions to such altitudes on physiological systems, including the ocular system, in children is scarce. Retinal vessels are embryologically of the same origin as vessels in the brain, and have similar anatomical and physiological characteristics. Thus, any hypoxia-related changes in the morphology of the former may reflect the status of the latter. Objective: To compare the effect of one-day hypoxic exposure, equivalent to the elevation of high-altitude ski resorts in North America and Europe (∼3,000 m), on retinal vessel diameter between adults and children. Methods: 11 adults (age: 40.1 ± 4.1 years) and 8 children (age: 9.3 ± 1.3 years) took part in the study. They spent 3 days at the Olympic Sports Centre Planica (Slovenia; altitude: 940 m). During days 1 and 2 they were exposed to normoxia (FiO2 = 0.209), and day 3 to normobaric hypoxia (FiO2 = 0.162 ± 0.03). Digital high-resolution retinal fundus photographs were obtained in normoxia (Day 2) and hypoxia (Day 3). Central retinal arteriolar equivalent (CRAE) and venular equivalents (CRVE) were determined using an Automated Retinal Image Analyser. Results: Central retinal arteriolar and venular equivalents increased with hypoxia in children (central retinal arteriolar equivalent: 105.32 ± 7.72 µm, hypoxia: 110.13 ± 7.16 µm, central retinal venular equivalent: normoxia: 123.39 ± 8.34 µm, hypoxia: 130.11 ± 8.54 µm) and adults (central retinal arteriolar equivalent: normoxia: 105.35 ± 10.67 µm, hypoxia: 110.77 ± 8.36 µm; central retinal venular equivalent: normoxia: 126.89 ± 7.24 µm, hypoxia: 132.03 ± 9.72 µm), with no main effect of group or group*condition interaction. A main effect of condition on central retinal arteriolar and venular equivalents was observed (central retinal arteriolar equivalent:normoxia: 105.34 ± 9.30 µm, hypoxia: 110.50 ± 7.67 µm, p < 0.001; central retinal venular equivalent: normoxia: 125.41 ± 7.70 µm, hypoxia: 131.22 ± 9.05 µm, p < 0.001). Conclusion: A 20-hour hypoxic exposure significantly increased central retinal arteriolar and venular equivalents in adults and children. These hypoxia-induced increases were not significantly different between the age groups, confirming that vasomotor sensitivity of the retinal vessels to acute hypoxia is comparable between adults and prepubertal children.